The Effect of Value and Reference Group on Young Consumer’s Hedonic Buying - Diana Hartatin; Megawati Simanjuntak (Journal of Consumer Sciences, 2016)
Hedonic buying is one of buying behavior that based on happiness aspect, involved sensory and excluded needs. Hedonic buying can cause individual to be extravagant in long term period. The aim of this research was to analyze the effect of value and reference group on young consumer’s hedonic buying. The design of this research was cross sectional study with survey method answered by self-report questionnaire. The results were supported by an in-depth interview with some samples. This research involved 205 undergraduate students of Bogor Agricultural University which were selected by using proportional random sampling. Statistical analysis used in this study was independent t-test and multiple regression analysis. There was a significant difference on excitement value dimension and hedonic buying between man and woman. The variable of value had significant and positive influence on hedonic buying, meanwhile reference group did not influence significantly on hedonic buying.Keywords: hedonic buying, reference group, value  Pembelian hedonis merupakan suatu pembelian yang berdasarkan pada aspek kesenangan, melibatkan sensori dan diluar kebutuhan. Pembelian hedonis dalam jangka waktu panjang menyebabkan individu menjadi boros. Tujuan dari penelitian ini adalah menganalisis pengaruh nilai dan kelompok acuan terhadap pembelian hedonis konsumen muda. Desain penelitian ini menggunakan cross sectional study dengan metode survei secara self-report menggunakan kuisioner. Hasil penelitian didukung dengan wawancara mendalam terhadap beberapa contoh. Penelitian ini melibatkan  205 orang mahasiswa Strata-1 (S1) Institut Pertanian Bogor yang dipilih secara proportional random sampling. Analisis statistik yang digunakan adalah uji beda independent t-test dan analisis linear berganda. Terdapat perbedaan signifikan pada dimensi nilai kegembiraan dan pembelian hedonis antara laki-laki dan perempuan. Nilai berpengaruh secara signifikan  dan positif terhadap pembelian hedonis, sedangkan kelompok acuan tidak berpengaruh signifikan terhadap pembelian hedonis. Kata kunci: kelompok acuan, nilai, pembelian hedonis